2012
DOI: 10.1186/1471-2261-12-70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin therapy on the progression of coronary atherosclerosis

Abstract: BackgroundAn increasing number of authors employing intravascular ultrasound (IVUS) and virtual histology (VH-IVUS) have investigated the effect of statin use on plaque volume (PV) and plaque composition. However, inconsistent results have been reported. Therefore, we conducted a meta-analysis to determine the appropriate regimen of statins to effectively stabilize vulnerable coronary plaques.MethodsOnline electronic databases were carefully searched for all relevant studies. We compared mean values of PV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 72 publications
4
39
0
1
Order By: Relevance
“…Findings of the present analysis are consistent with those of a recent meta-analysis evaluating the effect of statins on the IVUS-derived progression of coronary atherosclerosis, which uncovered a 2-fold greater decrease in coronary atheroma volume in patients with ACS when compared with those with stable coronary disease after statins. 25 An explanation of these findings may relate to underlying differences in coronary atheroma composition in patients with ACS when compared with stable patients. Pathological and imaging studies have demonstrated the coronary tree of patients with ACS to contain greater amounts of lipid-laden plaque and inflammatory infiltrate, occurring diffusely, when compared with non-ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of the present analysis are consistent with those of a recent meta-analysis evaluating the effect of statins on the IVUS-derived progression of coronary atherosclerosis, which uncovered a 2-fold greater decrease in coronary atheroma volume in patients with ACS when compared with those with stable coronary disease after statins. 25 An explanation of these findings may relate to underlying differences in coronary atheroma composition in patients with ACS when compared with stable patients. Pathological and imaging studies have demonstrated the coronary tree of patients with ACS to contain greater amounts of lipid-laden plaque and inflammatory infiltrate, occurring diffusely, when compared with non-ACS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were only treated with intensive LLT for 12 months, and it is possible that the shorter follow-up period could have been the reason for the absent regression in total plaque volume. Importantly, a recent metaanalysis of IVUS studies showed that regression in total plaque volume is correlated with LDL levels and the duration of statin treatment [29]. Another explanation could be a potential lower sensitivity of CTA to detect changes in total plaque volume compared to IVUS.…”
Section: I) Effects Of Intensive Llt On Plaque Volumementioning
confidence: 99%
“…Inter-observer variability before alteration in plaque volume is seen [29]. Furthermore, emerging evidence suggests that statins possess a wide range of beneficial effects on the cardiovascular system, including endothelial stabilisation, attenuation of oxidative stress, and modification of the inflammatory response [9].…”
Section: Intra-observer Variabilitymentioning
confidence: 99%
“…5,22-25 Previous studies also showed that coronary plaque regression induced by statin therapy appeared to be more predominant in ACS patients than in non-ACS patients. [26][27][28] This may be related to the underlying differences in coronary plaque composition in patients with ACS compared with those with stable angina pectoris. In pathology and imaging studies, ACS patients have a larger percentage of lipid-laden plaque with inflammatory cells, 29 compared with a higher percentage of fibrocalcific plaque in patients with chronic stable lesions.…”
Section: Discussionmentioning
confidence: 99%